1990
DOI: 10.1017/s0003356100004967
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary inclusion of yeast culture on digestion in the sheep

Abstract: Six mature sheep, each fitted with a rumen cannula, were assigned to six diets in a 6 × 6 Latin-square design experiment to examine the effects of a yeast culture on ruminal metabolism, rumen liquid outflow rate, fibre digestion in the rumen and overall nutrient digestibility. The yeast culture (YC) was a commercial product composed of a yeast (Saccharomyces cerevisae) and the media on which it grew and dried so as to maintain its fermentative capacity. The six dietary treatments were three diets differing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
38
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 24 publications
6
38
0
1
Order By: Relevance
“…Published reports of the effect of yeast culture on production rates of SCFA are variable. Chademana and Offer (1990) reported that Yea-Sacc 1026 had no effect on total SCFA or SCFA composition, but others found stimulation in the proportion of propionate at the expense of acetate (Plata et al, 1994) or even an increase in the proportion of acetate (Mutsvangwa et al, 1992). In an in vitro study, Miller-Webster et al (2002) evaluated two yeast culture products (0.2 g/l, Diamond V XP yeast culture and 0.2 g/l, A-Max yeast culture) and both of them increased propionate concentration and reduced the ratio of acetate to propionate, similar to this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published reports of the effect of yeast culture on production rates of SCFA are variable. Chademana and Offer (1990) reported that Yea-Sacc 1026 had no effect on total SCFA or SCFA composition, but others found stimulation in the proportion of propionate at the expense of acetate (Plata et al, 1994) or even an increase in the proportion of acetate (Mutsvangwa et al, 1992). In an in vitro study, Miller-Webster et al (2002) evaluated two yeast culture products (0.2 g/l, Diamond V XP yeast culture and 0.2 g/l, A-Max yeast culture) and both of them increased propionate concentration and reduced the ratio of acetate to propionate, similar to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Some data indicate that supplementation of live yeast culture into the feed ration may improve feed intake (Williams et al, 1991), weight gain (Lesmeister et al, 2004), digestion (Wiedmeier et al, 1987), increase of anaerobic and cellulolytic bacteria (Wiedmeier et al, 1987;Koul et al, 1998), increase the ruminal pH (Williams et al, 1991;Koul et al, 1998) and alter the patterns of SCFA production (Wiedmeier et al, 1987). However, yeast cultures have not been found to alter ruminal fermentation or improve animal performance in all cases (Chademana and Offer, 1990). These inconsistencies might be due to straindependent, or specifi c differences between commercial additives, or differences in dietary compositions (Oeztuerk et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, Rode et al (1999) forneceram quantidade semelhante (23 g/dia) de enzimas para vacas e obtiveram aumento significativo na digestibilidade da MS, PB, FDN e FDA, comprovando que a resposta ao fornecimento de enzimas depende da quantidade fornecida. Chademana & Offer (1990), trabalhando com ovinos, e Pereira et al (2001), com novilhas, não verificaram efeito sobre a digestibilidade dos nutrientes, com adição de leveduras na dieta. Wiedmeier et al (1987) forneceram 90,0 g de levedura ou de extrato da fermentação de Aspergillus oryzae (AO), ou uma mistura de ambos (90 g de levedura e 2,6 g de AO), para vacas secas recebendo dieta com 50,0% de concentrado, e observaram aumento significativo na digestibilidade da MS, PB e hemicelulose.…”
Section: Tdn According Tounclassified
“…The addition of yeast culture to the ruminant diet may be an effective tool to modify ruminal fermentative pattern (Williams et al, 1991;Carro ef al, 1992); however, its effect on fiber digestion is still controversial (Chademana and Offer, 1990;Williams et al, 1991;Mir and Mir, 1994 At the end of the fermentation, cells were recovered by centrifugation at 10 000 x g for 15 5 min at 4°C, washed with bidistilled sterile water and resuspended in 1 ml of sterile water. The dry weight of the washed cell suspension was determined after drying at 105°C for 3 h as previously described (Russell, 1986).…”
mentioning
confidence: 99%